Farmer participation in supermarket channels, production technology, and efficiency: The case of vegetables in Kenya - Rao, E.J.O.; Brummer, B.; Qaim, M. (Wiley, 2012)
Supermarkets are gaining ground in agrifood systems of many developing countries. While recent research has analyzed income effects in the small farm sector, impacts on productivity and efficiency have hardly been studied. We use a meta-frontier approach and combine this with propensity score matching to estimate treatment effectsamongvegetable farmers in Kenya. Participation in supermarket channels increases farm productivity in terms of meta-technology ratios by 45%.We also find positive and significant impacts on technical efficiency and scale efficiency. Supermarket expansion therefore presents opportunities for agricultural growth in the small farm sector, which is crucial for poverty reduction in Africa.